1998
DOI: 10.3168/jds.s0022-0302(98)75843-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties of a Heparin-binding Peptide Derived from Bovine Lactoferrin

Abstract: A heparin-binding peptide was isolated from a proteolytic hydrolysate of bovine lactoferrin by affinity chromatography using an immobilized heparin column. Analysis of amino acid sequences at the N-terminus showed that this heparin-binding peptide is derived from the region beginning at the 17th amino acid residue of the bovine lactoferrin sequence. The molecular mass of this peptide was 3195.5 as measured by matrix-assisted laser desorption-time of flight mass spectrometry. This peptide is the same as the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 22 publications
0
43
0
Order By: Relevance
“…We also observed that LfcinB bound to immobilized heparin, consistent with earlier published findings. 30 However, LfcinB did not bind to immobilized bFGF or VEGF 165 , suggesting that a direct interaction between LfcinB and bFGF or VEGF 165 was not responsible for the antiangiogenic effect of LfcinB. Importantly, LfcinB binding to heparin was reduced in the presence of bFGF or VEGF 165 , suggesting that LfcinB, bFGF, and VEGF 165 might all interact with the same heparin-like binding sites on cell-surface heparan sulfate proteoglycans.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…We also observed that LfcinB bound to immobilized heparin, consistent with earlier published findings. 30 However, LfcinB did not bind to immobilized bFGF or VEGF 165 , suggesting that a direct interaction between LfcinB and bFGF or VEGF 165 was not responsible for the antiangiogenic effect of LfcinB. Importantly, LfcinB binding to heparin was reduced in the presence of bFGF or VEGF 165 , suggesting that LfcinB, bFGF, and VEGF 165 might all interact with the same heparin-like binding sites on cell-surface heparan sulfate proteoglycans.…”
Section: Discussionmentioning
confidence: 88%
“…44 LfcinB did not exhibit any cytotoxic activity against HUVECs, excluding the possibility that LfcinB simply caused HUVECs to undergo apoptosis, as occurs when various cancer cell lines are exposed to LfcinB. 24,27 Because both bovine lactoferrin and LfcinB are known to bind heparin, 29,30 our findings led us to hypothesize that LfcinB competed with bFGF and VEGF 165 for heparin-like binding sites on heparan sulfate proteoglycans on the surface of HUVECs. Heparan sulfate proteoglycans are required for bFGF and VEGF 165 binding and signaling through their respective cell-surface receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lactoferrin molecule is proposed to consist of two lobes (N-lobe and C-lobe) (40). The N-lobe contains the active domains for bactericidal action and heparin binding (31,41), whereas the C-lobe contains a functional domain for hepatocyte binding and internalization (42). In these previous studies, lactoferrin fragments were prepared by tryptic cleavage of lactoferrin and isolated by high performance liquid chromatography.…”
Section: Table II Effect Of Lactoferrin On the Saliva-induced Aggregamentioning
confidence: 99%